Efficacy of Foley Catheter Bulb with Intracervical Dinoprostone Gel versus Dinoprostone Gel Alone for Cervical Ripening and Induction of Labour: An Observational Study - Sohan Bhowmick; Nilratan Das; Tanmoy Das; Arunava Biswas (Journal of Clinical and Diagnostic Research, 2024)
Introduction: One of the most common obstetrical interventions is the induction of labour. Cervical ripening drugs are typically used before conventional methods of induction since they are linked to an increased risk of protracted labour, chorioamnionitis, and Caesarean Sections (CS) during labour induction when an unfavourable cervix is present. The two major techniques for cervical ripening are mechanical interventions, such as the insertion of balloon catheters, and the application of pharmacologic agents, such as prostaglandins. It is widely accepted that the induction of labour, which ultimately leads to vaginal delivery, is largely dependent on the condition of the uterus’ cervix. Aim: To compare the efficacy of a combination of Foley bulb catheter and intracervical Dinoprostone and intracervical Dinoprostone alone for the induction of labour. Materials and Methods: A prospective observational study was performed over 150 pregnant mothers from May 2018 to April 2019. in the labour room of North Bengal Medical College and Hospital, a tertiary care institution in Darjeeling, West Bengal, India. The pregnant women were divided into two groups: intracervical Dinoprostone gel alone (Group-1) and a combination of intracervical Foley catheter and intracervical Dinoprostone gel (Group-2) with n=75 patients in each group. Group-1 received intracervical Dinoprostone gel 0.5 mg, which was repeated every 6 hours, a maximum of three doses, or until she went into active labour, whichever occurred earlier. In Group-2, a 16 F Foley catheter was inserted into the cervix, inflated, and a single dose of intracervical Dinoprostone gel 0.5 mg was given alongside it. Participant demographic characteristics, medical and pregnancy history, indication for labour induction, labour course, and outcomes were collected. The collected data were analysed with the mean and standard deviation for numerical variables and counts and percentages for categorical variables. Odds ratio was calculated where deemed relevant. Results: The induction to delivery time was considered the primary outcome and was shorter in Group-2 by 28 minutes (p=0.342). Among the secondary outcomes, the duration of the latent phase of labour was shorter in Group-2 by 57 minutes, and the proportion of patients delivering within 12 hours was also higher (28%) but statistically insignificant (p>0.05). The rates of CS were unaffected by the mode of induction. None of the two methods were found to be inferior to the other in respect to neonatal outcomes or complications of labour like chorioamnionitis and postpartum haemorrhage. Conclusion: The combination of Foley catheter with intracervical Dinoprostone gel did not prove to be more efficient than intracervical Dinoprostone alone for labour induction in the current study.